2021
DOI: 10.1002/ddr.21835
|View full text |Cite
|
Sign up to set email alerts
|

CircMYLK promotes the growth, migration, invasion, and survival of bladder cancer cells by upregulating CCND3 level via competitively binding to miR‐34a

Abstract: Bladder cancer is one of the most common types of urothelial carcinoma with a rising incidence rate worldwide. Circular RNAs (circRNAs) are involved in the development of numerous cancers, including bladder cancer. We aimed to uncover the role and associated mechanism of circMYLK in bladder cancer. The expression levels of cir-cMYLK, miRNA-34a (miR-34a) and Cyclin D3 (CCND3) mRNA were investigated using real-time quantitative polymerase chain reaction. The protein level of CCND3 was investigated using western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Moreover, one review article and one investigation with only bioinformatic analysis were excluded after full‐text reviews (Figure 1 ). Ultimately, 12 studies were included in the qualitative synthesis of this review 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 21 , 22 (Table 1 ); however, three studies did not provide data regarding prognostic or clinicopathological features 12 , 21 , 22 ; therefore, nine articles were included in the meta‐analysis. Seven of these studies investigated the prognostic significance of circMYLK, and nine studies ascertained the clinicopathological importance of circMYLK in patients with malignancies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, one review article and one investigation with only bioinformatic analysis were excluded after full‐text reviews (Figure 1 ). Ultimately, 12 studies were included in the qualitative synthesis of this review 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 21 , 22 (Table 1 ); however, three studies did not provide data regarding prognostic or clinicopathological features 12 , 21 , 22 ; therefore, nine articles were included in the meta‐analysis. Seven of these studies investigated the prognostic significance of circMYLK, and nine studies ascertained the clinicopathological importance of circMYLK in patients with malignancies.…”
Section: Resultsmentioning
confidence: 99%
“…All studies were from China and published between 2017 and 2021. Using the quantitative real‐time polymerase chain reaction (qRT‐PCR), the studies revealed upregulation of circMYLK in different malignant tissue samples, including bladder cancer, 7 , 8 HCC, 10 , 11 laryngeal cancer, 12 , 13 NSCLC, 9 renal cancer, 14 ovarian cancer, 15 prostate cancer, 22 cervical cancer, 21 and colorectal cancer. 16 According to these studies, circMYLK acts as a tumor promoter circRNA leading to migration, invasion, proliferation, and metastasis of neoplastic cells and inhibiting their apoptosis through interaction with several miRNAs and corresponding downstream signaling pathways.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CircCEP128 deficiency represses the progression of BC through modulating themicroRNA-515-5p/SDC1 Axis [ 17 ]. CircMYLK increases the expression of CCND3 to facilitate the proliferation and metastasis of BC cells through sponging miR-34a [ 18 ]. CircNT5E speeds up the progression of BC by sponging miR-502-5p [ 19 ].…”
Section: Introductionmentioning
confidence: 99%